2021
DOI: 10.1101/2021.04.05.438444
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Co-infection of chickens with H9N2 and H7N9 avian influenza viruses leads to emergence of reassortant H9N9 virus with increased fitness for poultry and enhanced zoonotic potential

Abstract: An H7N9 low pathogenicity avian influenza virus (LPAIV) emerged through genetic reassortment between H9N2 and other LPAIVs circulating in birds in China. This virus causes inapparent clinical disease in chickens, but zoonotic transmission results in severe and fatal disease in humans. We evaluated the consequences of reassortment between the H7N9 and the contemporary H9N2 viruses of G1 lineage that are enzootic in poultry across the Indian sub-continent and the Middle East. Co-infection of chickens with these … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 100 publications
0
10
0
Order By: Relevance
“…demonstrated that the acquisition of PB2 627K in mammals is driven by the low polymerase activity attributed to PA. 49 Moreover, Bhat et al showed that acquiring the PA gene from an H9N2 virus dramatically increased the polymerase activity of an H7N9 virus in human cells. 50 In terms of the rapid evolution and active reassortment of H10N3 in nature, 23,40,41 the presence of avian adaptation marker PB2 627E does not downgrade the potential cross-species transmission of H10N3 viruses.…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that the acquisition of PB2 627K in mammals is driven by the low polymerase activity attributed to PA. 49 Moreover, Bhat et al showed that acquiring the PA gene from an H9N2 virus dramatically increased the polymerase activity of an H7N9 virus in human cells. 50 In terms of the rapid evolution and active reassortment of H10N3 in nature, 23,40,41 the presence of avian adaptation marker PB2 627E does not downgrade the potential cross-species transmission of H10N3 viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Serological analysis was undertaken as previously described for the sera of turkey [24] and chicken [23]. Ferret sera were treated with four volumes of receptor-destroying enzyme (APHA Scientific, Weybridge, UK) as previously described [22]. Detection of seroconversion to subtype-specific (homologous) HA antigens was conducted using the HAI assay, using four haemagglutination units of the corresponding H7N9 LPAIV as the antigen [30].…”
Section: Serologymentioning
confidence: 99%
“…One ferret from each block (total of two ferrets) was culled at 6 dpi for immunohistochemistry (IHC) analysis. For each ferret, the external nasal tissues were washed with 1 ml of PBS on 2, 3, 4, 5, 6, 7 and 8 dpi; 1 ml of PBS was used to wash the internal nasal cavity on days 2, 4, 6 and 8 dpi, as previously described [22,34]. Blood was collected from all remaining ferrets at the end of the experiment at 14 dpi, for serological testing.…”
Section: Ferret Model Of Zoonosis and Reverse Zoonosismentioning
confidence: 99%
“…These are perhaps more likely for pathogens with multi-segmented genomes such as the influenza virus, where rapid viral replication can increase diversity by allowing the recombination of different genomic segments ( McDonald et al, 2016 ). Revealing the plausible ecological contexts that increase the chances of reassortment (e.g., presence of co-infecting strains; Tao et al, 2015 ) might be crucial to tracing how novel genome combinations can arise to create influenza subtypes with expanded host range and novel antigenic properties ( Bhat et al, 2021 ; also see Cecilia, 2014 for recombined dengue virus genotypes).…”
Section: Role Of Tolerance In Spillover and New Infectionsmentioning
confidence: 99%
“…Step 2: Tolerant hosts with reduced inflammatory responses can support the circulation of diverse pathogen species and strains. A longer infectious period within tolerant hosts also provides an accurate ecological niche where pathogens can acquire newer mutations over time or undergo genetic exchanges and re-assortments to produce novel variants ( Bhat et al, 2021 ; Domingo-Calap, 2019 ). Step 3: Although the risk of infecting a new host species (other than the natural reservoir species) might be low, some of these pathogen variants with altered genetic backgrounds might be able to cross the species barrier and infect a new host more effectively ( Mandl et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%